Nutrient Content and Distribution in Milling Fractions of Rice Grain - Resurrection, Adoration P.; Juliano, Bienvenido O.; Tanaka, Yonemi (Wiley, 1979)
Nutrient content and distribution in a low‐protein (7.5%) rice and a high‐protein (10.8 %) rice were studied by analysing successive abrasive milling fractions of brown rice. Non‐starch constituents decreased from the surface to the centre of the grain in both rices, except that the highest protein fraction in high‐protein rice was the sub‐aleurone layer. Starch and amylose contents of starch increased progressively from the surface to the centre of the grain and were lower in high‐protein grain. Although this low‐protein rice had lower total ash content than the high‐protein rice, other samples of the same low‐protein rice had comparable ash content to the high‐protein rice. Glutelin accounted for 87–93% of milled rice protein. Protein and protein bodies of the sub‐aleurone layer and inner endosperm have similar amino‐grams, and electrophoretic patterns using analytical and SDS‐polyacrylamide disc gels.